New terebellids (Polychaeta: Terebellidae) from northeastern Brazil - Santos, Andre Ssouza Dos; de Matos Nogueira, João Miguel; Fukuda, Marcelo Veronesi; Christoffersen, Martin Lindsey (Zootaxa, 2010)
Four new species of terebellid polychaetes were collected at the Reserva de Desenvolvimento Sustentável da Ponta de Tubarão, State of Rio Grande do Norte, northeastern Brazil. These species are Streblosoma patriciae sp. nov., Terebella leslieae sp. nov., Nicolea ceciliae sp. nov., and Pista alonsae sp. nov. All these species are herein described and compared with the morphologically most similar congeners.